Characterization of the emerging clinically-relevant multidrug-resistant Salmonella enterica serotype 4,[5],12:i:-(monophasic variant of S. Typhimurium) clones (monophasic variant of S. Typhimurium) clones - Mourão, J. (2014)
To better understand the recent success/emergence of Salmonella enterica serotype 4,[5],12:i:- we characterized the population diversity, fljAB deletion patterns, antibiotic resistance features and associated genetic elements of a comprehensive collection obtained in the last decade from Portugal (2002-2010). One hundred thirty-one isolates from human clinical specimens, food, environment and piggeries, verified by PCR as S. 4,[5],12:i:-, were studied for clonality (Pulsed-Field Gel Electrophoresis and Multilocus Sequence Typing), antibiotic resistance by phenotypic (disk diffusion and/or agar dilution) and genotypic (PCR/Restriction Fragment Length Polymorphism and sequencing, genomic location) methods and fljAB-deletions (PCR). Plasmid analysis included determination of size, content and characterization of the incompatibility group (PCR-Based Replicon Typing and I-CeuI/S1-hybridization). Results showed three multidrug-resistant (MDR) clones circulating and causing infections, associated with particular phenotypic and genotypic features. Most of the isolates belonged to the widespread European (ASSuT phenotype, RR1-RR2 resistance regions, ST34) and Spanish (carrying a sul3-type III integron within IncA/C plasmids, ST19) clones circulating in Europe. A third clone, here designated Southern European clone (carrying a sul3-type I integron within IncR plasmids, ST19), presents a fljAB region different from the previous clones and similar to the US strains, despite differences in the MDR mobile genetic platforms. The success of S. 4,[5],12:i:- might be related to the selective advantage offered by MDR profiles associated with stable genetic elements, also carrying virulence features, along with well adapted clones to the animal food production and causing human infections.